2012
DOI: 10.1007/s00401-012-0980-x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA polymorphisms specifically modify cerebral β-amyloid proteostasis

Abstract: Several lines of evidence link mutations and deletions in mitochondrial DNA (mtDNA) and its maternal inheritance to neurodegenerative diseases in the elderly. Age-related mutations of mtDNA modulate tricarboxylic cycle enzyme activity, mitochondrial oxidative phosphorylation capacity and oxidative stress response. To investigate the functional relevance of specific mtDNA polymorphisms of inbred mouse strains in the proteostatic regulation of the brain, we established novel mitochondrial congenic mouse lines of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 39 publications
(49 reference statements)
2
44
1
Order By: Relevance
“…These findings add to evidence suggesting that impaired clearance of Aβ might be a crucial factor in sporadic Alzheimer disease-a view seconded at the meeting by data presented by Jens Pahnke (U. Magdeburg and DZNEMagdeburg, Germany), who showed that loss of ABC transporters B1 and C1, which extrude Aβ from the CNS parenchyma, can lead to a substantial increase in Aβ-load [24]. These transporters not only are regulated by mitochondria [25], but also have a substantial impact on cerebral regeneration [26]. Thus, future investigations into toxic protein aggregation will have to consider production, as well as clearance, and hence the homeostatic contributions of the immune system and tissue barriers, such as the neurovascular unit or the choroid plexus.…”
Section: Translation Meets Systems Medicinesupporting
confidence: 73%
“…These findings add to evidence suggesting that impaired clearance of Aβ might be a crucial factor in sporadic Alzheimer disease-a view seconded at the meeting by data presented by Jens Pahnke (U. Magdeburg and DZNEMagdeburg, Germany), who showed that loss of ABC transporters B1 and C1, which extrude Aβ from the CNS parenchyma, can lead to a substantial increase in Aβ-load [24]. These transporters not only are regulated by mitochondria [25], but also have a substantial impact on cerebral regeneration [26]. Thus, future investigations into toxic protein aggregation will have to consider production, as well as clearance, and hence the homeostatic contributions of the immune system and tissue barriers, such as the neurovascular unit or the choroid plexus.…”
Section: Translation Meets Systems Medicinesupporting
confidence: 73%
“…This functional activation is limited by a still unknown mechanism and leads to a 'hibernating' microglia species enclosed the growing amyloid deposits. The phagocytosis function is not only modulated by amyloid-beta but also by specific mitochondrial activity changes [34] that show a direct relation of cerebral ATP levels and microglia activity. A current report demonstrated that CCR2 deficiency in the transgenic mouse model of Alzheimer's disease provokes a rapid cognitive impairment closely correlated with brain amyloid pathology [35].…”
Section: Multiple Sclerosis Eae and Alzheimer's Diseasementioning
confidence: 99%
“…Paraffi n-embedded, 4-μm-thick sections were deparaffi nized and conventionally stained with hematoxylin-eosin (H&E) stain. Immunohistochemical analysis was performed according to our previous publications [52][53][54][55][56][57][58] using a BOND-MAX (Leica Microsystems GmbH/Menarini, Germany) with antibodies against ionized calcium-binding adapter molecule 1 (IBA1, 1:2,000, Wako 019-19741, Germany) to label microglia, glialfi brillary acid protein (GFAP, 1:1,000, DAKO Z033401, Germany) to label astrocytes, myelinbasic protein (MBP, 1:1,600, DAKO A062301, Germany) to label myelin sheets, neurofi lament (NF200; 1:160, Sigma-Aldrich N4142-.5ML, Germany) to label axons, NeuN (1:1,000, Millipore MAB377, Germany) to label neurons, and anti-Toxo (1:200, Dianova DLN-16734, Germany) to label T. gondii. Slides were developed using the Bond™ Polymer Refi ne Detection kit (Menarini/Leica, Germany).…”
Section: Histopathologymentioning
confidence: 99%